Feeding turbot juveniles Psetta maxima L. with increasing dietary plant protein levels affects growth performance and fish welfare. (29th September 2014) - Bonaldo, A.; Di Marco, P.; Petochi, T.; Marino, G.; Parma, L.; Fontanillas, R.; Koppe, W.; Mongile, F.; Finoia, M.G.; Gatta, P.P.
Abstract A 9‐week feeding trial was performed to evaluate the effects of fishmeal (FM) replacement by a mixture of plant proteins (PP), consisted of wheat gluten, soybean meal and soy protein concentrate, on the growth performance and welfare of turbot juveniles (initial weight 9.7 ± 0.2 g). Four isonitrogenous and isolipidic diets contained FM at 500 g kg−1 (FM50), 350 g kg−1 (FM35), 200 g kg−1 (FM20) and 50 g kg−1 (FM5). A decreased feed intake and an increased feed conversion rate was observed in FM5 group. Specific growth rate was significantly reduced in FM20 and FM5 groups, whereas protein and lipid utilization and proximate whole body composition were significantly different in FM5 group. Serum cortisol significantly increased in FM20 and FM5 groups whereas cholesterol, triglycerides, NEFA, total protein and urea concentrations significantly decreased. Serum lysozyme and blood phagocytes increased in FM20 and FM5 groups. FM35 ensured growth close to FM50, without significant effects on health and welfare of animals. FM20 and FM5 groups displayed reduced growth, metabolic stress and an immune response with effects on health and welfare. Results highlighted the consistency between growth performance and welfare status, suggesting the usefulness of their combined assessment for evaluating the suitability of PP and to improve dietary formulation for turbot.